2006
DOI: 10.1016/j.ydbio.2006.03.024
|View full text |Cite
|
Sign up to set email alerts
|

A reporter-assisted mutagenesis screen using α1-tubulin-GFP transgenic zebrafish uncovers missteps during neuronal development and axonogenesis

Abstract: Alpha1-tubulin expression occurs in a neural-specific, temporally regulated, and regeneration-inducible fashion in zebrafish. A GFP reporter driven by the alpha1-tubulin promoter in transgenic zebrafish acts as a stable, in vivo molecular tag that follows neuronal development from birth/specification through postmitotic differentiation to axonal outgrowth and synaptogenesis. We exploited this transgenic system in a reporter expression-dependent (morphology-independent) mutagenesis screen to identify disruption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 84 publications
1
24
0
Order By: Relevance
“…These genes are only expressed in the central nervous system during early developmental stages, and can be considered as biomarkers for developmental neurotoxicity (Fan et al, 2010). These genes encode proteins that play important roles for myelination of axons (e.g., mbp) (Yoshida and Macklin, 2005), formation of microtubules (e.g., α1-tubulin) (Gulati-Leekha and Goldman, 2006), and regulation of the astrocyte cytoskeleton (e.g., gfap) (Nielsen and Jorgensen, 2003) in the developing central nervous system. Down-regulation of expression of these genes was only observed in the co-exposure groups, suggesting a detrimental impact on cytoskeleton regulation, neuronal myelination, and neuron growth during central nervous system development.…”
Section: Discussionmentioning
confidence: 99%
“…These genes are only expressed in the central nervous system during early developmental stages, and can be considered as biomarkers for developmental neurotoxicity (Fan et al, 2010). These genes encode proteins that play important roles for myelination of axons (e.g., mbp) (Yoshida and Macklin, 2005), formation of microtubules (e.g., α1-tubulin) (Gulati-Leekha and Goldman, 2006), and regulation of the astrocyte cytoskeleton (e.g., gfap) (Nielsen and Jorgensen, 2003) in the developing central nervous system. Down-regulation of expression of these genes was only observed in the co-exposure groups, suggesting a detrimental impact on cytoskeleton regulation, neuronal myelination, and neuron growth during central nervous system development.…”
Section: Discussionmentioning
confidence: 99%
“…Western blotting assay further demonstrated that acute PBDE exposure had an effect on protein in the brain. The genes of mbp (a marker of myelination) and a1-tubulin (a neuron-specific microtubule) are expressed exclusively in the nervous system of developing zebrafish larvae [42,43]. Sonic hedgehog a is a morphogen that patterns many organ systems (including the nervous system) and is considered an important signaling molecule in zebrafish embryogenesis [44].…”
Section: Discussionmentioning
confidence: 99%
“…Mutants in this broader class displayed brain hemorrhaging with mild additional cardiovascular defects and several of these mutants remain to be characterized. 14,41 Genetic mapping of bubblehead (bbh) and redhead (rhd) revealed that the genetic lesions were positioned in p21-activated kinase (Pak)-interacting exchange factor protein β (βpix) 42 and p21-activated kinase2a (pak2a), 43 respectively. In vitro studies had previously provided evidence of a βPix-Pak interaction acting upstream of the small GTPase Rac to induce cell motility.…”
Section: Endothelial Cell-cell Adhesion In Developmentmentioning
confidence: 99%